2023
DOI: 10.3389/frph.2023.1120937
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of the Congo Red Dot paper test in hypertensive disorders of pregnancy: A systematic review and meta-analysis

Abstract: BackgroundCongo Red Dot Paper Test (CRDPT) appears to be a simple, cost-effective, non-invasive diagnostic tool for hypertensive disorders of pregnancy (HDP). The main objective of the study is to assess the effectiveness of CRDPT in detecting HDP.MethodsThis is a systemic review and meta-analysis of published studies on the effectiveness of CRDPT in the detection of HDP. The study was conducted in line with the PRISMA-DTA guidelines. The PICOS framework was used to search for relevant articles using Medline, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
(89 reference statements)
0
3
0
Order By: Relevance
“…The Congo red dot (CRD) test represents a non-invasive and low-cost alternative to other methods of assessing protein misfolding load associated with PE. The clinical applicability of the CRD test, which is based on the detection of urine congophilia, as established by our lab, has been examined in fourteen studies, including one randomized control trial and one meta-analysis ( [90,91,[204][205][206][207][208][209][210][211][212][213][214][215]). In one study, our lab evaluated the performance of the CRD test at measuring misfolded protein load in urine and serum against that of Thioflavin-T (ThT)-enhanced fluorescence, a benzothiazole dye that preferentially binds to amyloid fibrils [214].…”
Section: Early Prediction and Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…The Congo red dot (CRD) test represents a non-invasive and low-cost alternative to other methods of assessing protein misfolding load associated with PE. The clinical applicability of the CRD test, which is based on the detection of urine congophilia, as established by our lab, has been examined in fourteen studies, including one randomized control trial and one meta-analysis ( [90,91,[204][205][206][207][208][209][210][211][212][213][214][215]). In one study, our lab evaluated the performance of the CRD test at measuring misfolded protein load in urine and serum against that of Thioflavin-T (ThT)-enhanced fluorescence, a benzothiazole dye that preferentially binds to amyloid fibrils [214].…”
Section: Early Prediction and Diagnosismentioning
confidence: 99%
“…In addition, the CRD test was not efficient at predicting PE in a term asymptomatic cohort (UK) and was determined to have low sensitivity at predicting impending MIDPE (within 28 days of initial assessment) in a randomized control trial, as well as low sensitivity at predicting adverse maternal and neonatal outcomes in women presenting with symptoms of suspected PE [205,206,210]. Finally, in a meta-analysis that included five studies, Khaliq et al concluded that the test is ineffective based on forest plot analysis [204]. Of note, the five studies compared in the meta-analysis comprised highly heterogeneous patient populations.…”
Section: Early Prediction and Diagnosismentioning
confidence: 99%
“…Thus, pregnant women with preexisting renal disease unrelated to pregnancy can yield positive results in the CRD tests. Conversely, when proteinuria is absent in cases of preeclampsia, the CRD test may also have reduced effectiveness, as evidenced by a recent meta-analysis [23].…”
Section: Plos Onementioning
confidence: 99%